Enhancing Social Media Usage on Business Performance: MSEMs During The COVID-19 Pandemic in Indonesia - Seprianti Eka Putri (UIN Mataram, 2021)
The purpose of this study is to examine the impact of the increase in social media users on business performance in micro, small, and medium-sized enterprises (MSMEs). This research uses a quantitative approach, with an analytical tool SEM PLS. A total of 250 responses social media users collected from respondents through purposive sampling technique with data collection used an online questionnaire. With research findings, perceived utility, and perceived ease of use, compatibility all influence social media use. Further, The usage of social media for marketing has a positive effect on the business performance of SMEs in terms of improving sales, customer relations, productivity, and creativity. The contribution of this study is to provide more relevant insights into the usage of social media on SMEs in Indonesia that are directly affected by the COVID-19 outbreak.